Sarah Morton's day : a day in the life of a pilgrim girl - Waters, Kate.; Kendall, Russ (New York : Scholastic, 1989)
Text and photographs of Plimouth Plantation follow a pilgrim girl through a typical day as she milks the goats, cooks and serves meals, learns her letters, and adjusts to her new stepfather.
"A Blue Ribbon book.".
Includes index.
Booklist.
Elem. School Library Collection.
Wilson's Children.
3.3
Keywords: Children -- Massachusetts -- History -- 17th century -- Pictorial works -- Juvenile literature; Pilgrims (New Plymouth Colony) -- Pictorial works -- Juvenile literature; Children -- Massachusetts -- History; Pilgrims (New Plymouth Colony); Children -- Massachusetts -- History; Pilgrims (New England colonists); Pilgrims (New England colonists) -- Pictorial works; Massachusetts -- Social life and customs -- To 1775 -- Pictorial works -- Juvenile literature; Massachusetts -- Social life and customs; Massachusetts -- Social life and customs